Implementation of the “JASBUG” Mobile App as a Tool for Improving Students’ Physical Fitness - Arifah Kaharina; Muchamad Arif Al Ardha; Afifan Yulfadinata; Novadri Ayubi; Heryanto Nur Muhammad (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract: Physical fitness among Indonesian junior high school students remains uneven, ranging from good to very poor categories across different schools and regions, including Surabaya, East Java. The Indonesian government addressed this issue by introducing the Tes Kebugaran Pelajar Nusantara (TKPN) as a standardized fitness assessment instrument, yet physical education teachers still face two major challenges: limited mastery of the new testing procedure and reliance on manual, error-prone score recording. This community service program trained and introduced the "JASBUG" mobile application, designed to automate TKPN data recording and score conversion, to 12 physical education teachers from junior high schools in Surabaya who are members of the East Java Provincial National Sports Teachers Association (IGORNAS). The program adopted a single-cycle participatory training approach, combining hands-on TKPN practice with direct simulation of the JASBUG application, evaluated through pre-test and post-test instruments. Results showed a statistically significant increase in teachers' knowledge of TKPN procedures (mean score from 8.25 to 9.50; p=0.004). Participants also rated the JASBUG application highly across usability, functionality, reliability, usefulness, and user satisfaction (4.42–4.69 out of 5). These findings indicate the training and application successfully addressed both the knowledge gap and the administrative burden previously reported by teachers.